Cultivating a Sustainable Mindset in Higher Education - Martina, Tomičić Furjan; Hrustek, Larisa; Sakač, Nikola (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Recognizing the critical role that sustainability plays in shaping the future, this study examines various strategies for embedding sustainability into extracurricular programs to enhance student awareness, engagement, and action. This paper highlights successful initiatives that promote environmental stewardship and social responsibility, demonstrating that incorporating sustainability into extracurricular activities not only enriches the educational experience but also nurtures a generation of mindful and proactive leaders. By fostering and encouraging thereby cross-disciplinary collaborations, educators are called to action to prioritize sustainable development in different aspects and areas, ensuring the next generation is equipped to tackle global challenges and contribute to a sustainable future.